Inotropic and chronotropic effects of methanol extract of Aquilaria agallocha on rabbit heart (Bangladesh Journal of Pharmacology, 2013)
Aquilaria agallocha Roxb. (Thymelaeceae) heartwood is used in cardiac failure; however, its cardiotonic properties are poorly understood at a pharmacological level. This study investigated methanol extract of A. agallochafor presence of glycosides and its effects on force of contraction, heart rate and coronary flow on rabbit isolated heart. Furthermore, contribution of β1-adrenoceptors and/or L-type Ca2+ channels in A. agallocha-induced cardiac effects was explored. A. agallocha extract, digoxin, verapamil and metoprolol were administered in a retrograde manner. Force of contraction and heart rate were recorded with a force transducer attached to the heart. Coronary flow was measured from collected effluent. The extract induced a significant increase in force of contraction (p